Get Ahead with Quizizz Paper Mode: Improving Reading Comprehension of EFL Students - Daniati, Winda; Amri , Zul (Universitas Lancang Kuning, 2025)
This study explores the impact of Quizizz’s Paper Mode on the reading comprehension of English as a Foreign Language (EFL) students, addressing a gap in the literature regarding this relatively new feature. Despite the widespread use of Quizizz in digital education, its Paper Mode, which incorporates barcode scanning to assess student responses on printed quizzes, remains under-explored. Using an experimental design, the study involved two groups of eighth-grade students: an experimental group using Quizizz Paper Mode and a control group utilizing conventional media for reading comprehension activities. A total of 16 students participated, with 8 students in each group. The research employed a pre-test to measure baseline reading comprehension and a post-test to evaluate the effect of the intervention. Statistical analysis, specifically independent sample t-tests, revealed a significant difference in the post-test scores between the two groups (p=0.035), indicating that students in the experimental group showed greater improvement in reading comprehension compared to those in the control group. These results highlight the potential of Quizizz Paper Mode as an effective tool for enhancing reading comprehension, suggesting its efficacy in integrating digital features with traditional paper-based assessments. The study’s findings contribute to the understanding of hybrid learning environments, illustrating how innovative educational tools like Quizizz Paper Mode can support meaningful learning experiences and improve student performance. This research underscores the growing importance of incorporating advanced media in educational practices to foster engagement and achievement in EFL classrooms.